Multimorbidity and disease severity by age groups, in inpatients: cross-sectional study - Broeiro-Gonçalves, Paula (2019)
ABSTRACT - Introduction: Multimorbidity (MM) by age groups curves behaviour and its relationship with disease severity are not well established. Considering the Charlson Index as a prognosis instrument to measure disease severity, the objectives were to characterise the MM and its severity through the Charlson index in Portuguese inpatients. Methods: A cross-sectional, descriptive study with an analytical component was drawn through data exported from the hospitalisations Homogeneous Diagnostic Groups database of the Portuguese-NHS during the year 2015. The study included 22 chronic health conditions: the 15 predicted in the Charlson index and 7 more (hypertension, obesity, dyslipidaemia, osteoarthritis, osteoporosis, anxiety and depression). The bi and multivariable analyses were performed through the generalised linear model considering binary logistic regression. In the analysis, the IBM SPSS version 24.0 tool was used. Results: A total of 800,376 hospitalisations were analysed, from which 42% (336,398) corresponds to males and 58% (463,978) to females. The average age of the sample was 59.8 years, being higher in men (62.34 years) than in women (57.95 years). The mean number of diagnostics per person was 1.6, being greater in men (1.8). Disease severity was also higher in males. The greatest disease severity (Charlson > 5) occurred at middle-aged (between 55 and 74 years). Throughout life behaviour of the average number of conditions and the average Charlson index without adjustment for age is similar. By the weight attributed to age, the Charlson index age-adjusted shows a sharper tendency of elevation after the forty years. The distribution by age groups of the age-adjusted Charlson index, categorised according to the cut-offs defined in the methodology (cut-off 0 to < 5; cut-off 5 to < 9; cut-off ≥9), showed an abrupt growth for the cut-off ≥9 at 55/59 years, peaking at 75/79 years, while for cut-off 5 at < 9 the most marked growth occurs at 65/69 and the peak about 5 years later than for the cut-off ≥9. After the 90 years old all measures averages (MM and severity disease) suffer a decline. Discussion: The results suggest that the greatest disease severity are male associated and occurred at middle ages. There was an association between any MM measure and the Charlson index. The MM curves behaviour showed a decline in nonagenary age, suggesting healthy people live longer. Questioned if the MM and its severity is not a middle age health issue. As limitations, we identified its cross-sectional design and the omission of socioeconomic information and the use of the same medical conditions to measure MM and disease severity. Other studies and analysis models should explore the complexity of the MM phenomenon and its impact on long life.